2020
DOI: 10.17718/tojde.849885
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Flipped Classroom Approach on the Writing Achievement and Self-Regulated Learning of Pre-Service English Teachers

Abstract: The major purpose of this study is to investigate the impact of flipped classroom on pre-service English teachers' Advanced Writing achievement. The study also aims at exploring whether flipped classroom approach makes a difference, if any, on the self-regulated learning of the participants. The participants of this study were selected by convenience sampling method and consisted of fifty-five (N=55) pre-service ELT teachers attending Advanced Writing course and studying at English Language Teaching Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…In fact, the basic concept of face-to-face lectures remains the same as digital lectures. In a recent study, it was stated that flipped classroom approach did not reduce the effectiveness of the traditional teaching method (Altas & Mede, 2020). This proves that online lectures do not reduce the quality of student learning at all.…”
Section: Aspect 1 Planningmentioning
confidence: 98%
“…In fact, the basic concept of face-to-face lectures remains the same as digital lectures. In a recent study, it was stated that flipped classroom approach did not reduce the effectiveness of the traditional teaching method (Altas & Mede, 2020). This proves that online lectures do not reduce the quality of student learning at all.…”
Section: Aspect 1 Planningmentioning
confidence: 98%
“…According to the facts, through the use of mastered knowledge and effective reasoning, the problem of M can be solved [14].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…This review of the small body of literature combining SRL and MW shows the mixture of correlational studies that examined relations between SRL and writing performance/quality (Farsani et al, 2014;Zhang, 2016, 2018;Han et al, 2021), four intervention studies reporting on students' writing quality and some SRL skills (Fathi and Feizollahi, 2020;Teng and Zhang, 2020;Altas and Mede, 2021;Chen et al, 2021), or proposed untested SRL writing programs/instructional practices (Oxford, 2011;Andrade and Evans, 2013). While these lines of research contribute to our understanding of how SRL associates with MW and four intervention studies provide initial evidence of improvement in MW and SRL skills, they do not provide conclusive results on how SRL writing instructional methods work in authentic settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has shown that SRL is associated with improved performance by native speakers of English across disciplines and age-groups (Graham, 2006;De Corte et al, 2011;Kitsantas and Kavussanu, 2011;Tonks and Taboada, 2011), research on the usefulness of SRL instruction in developing scholarly writing skills in college students, especially ELs, is scarce and under-developed. A small number of scholars have recognized the importance of SRL in developing writing skills of ELs (Oxford, 2011;Andrade and Evans, 2013;Teng and Zhang, 2016, 2018Fathi and Feizollahi, 2020;Altas and Mede, 2021;Han et al, 2021). Research shows that the SRL processes that occur during writing by ELs are similar to those of native speakers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation